2018
DOI: 10.1108/rpj-06-2016-0103
|View full text |Cite
|
Sign up to set email alerts
|

Wind tunnel testing of additive manufactured aircraft components

Abstract: Purpose This paper aims to report on the physical distortions associated with the use of additive manufactured components for wind tunnel testing and procedures adopted to correct for them. Design/methodology/approach Wings of a joined-wing test aircraft configuration were fabricated with additive manufacturing and tested in a subsonic closed-loop wind tunnel. Wing deflections were observed during testing and quantified using image-processing procedures. These quantified deflections were then incorporated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Aghanajafi and Daneshmand (2010) compared the performance of 3D printed models with conventional metallic models in the same wind tunnel test environment, they concluded that the additive manufactured model could be used for a preliminary test to obtain initial aerodynamic database with much less time and cost. Teo et al (2018) conducted wind tunnel study on unconventional joined-wing models manufactured by 3D printing. Although the wing deflections were observed, they could be accounted for systematically.…”
Section: Introductionmentioning
confidence: 99%
“…Aghanajafi and Daneshmand (2010) compared the performance of 3D printed models with conventional metallic models in the same wind tunnel test environment, they concluded that the additive manufactured model could be used for a preliminary test to obtain initial aerodynamic database with much less time and cost. Teo et al (2018) conducted wind tunnel study on unconventional joined-wing models manufactured by 3D printing. Although the wing deflections were observed, they could be accounted for systematically.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the nylon parts were smoothed down by hand with 2000 grit sandpaper till they were smooth to touch. Previous experience 32 with this method of fabrication justifies its use in this study. Minor gaps between the fastened pieces were filled with plasticine to ensure a smooth continuous surface.…”
Section: Fuselage Modelmentioning
confidence: 95%
“…Teo et al [6] found that additive manufacturing provides cost-effective wing components for wind tunnel test components with fast turn-around time. They can be used with confidence if the wing deflections could be accounted for systematically and accurately, especially at the region of aerodynamic stall [6].…”
Section: Introductionmentioning
confidence: 99%